2014
DOI: 10.1002/anie.201308794
|View full text |Cite
|
Sign up to set email alerts
|

Proximity‐Enabled Protein Crosslinking through Genetically Encoding Haloalkane Unnatural Amino Acids

Abstract: The selective generation of covalent bonds between and within proteins would provide new avenues for studying protein function and engineering proteins with new properties. New covalent bonds were genetically introduced into proteins by enabling an unnatural amino acid (Uaa) to selectively react with a proximal natural residue. This proximity-enabled bioreactivity was expanded to a series of haloalkane Uaas. Orthogonal tRNA/synthetase pairs were evolved to incorporate these Uaas, which only form a covalent thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
91
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 105 publications
(91 citation statements)
references
References 17 publications
0
91
0
Order By: Relevance
“…This increase in the thermal stability could be due to more covalent bonds between the monomers of crosslinked C1 enzyme than WT enzyme according to Xiang et al . 36 .
Figure 7SDS-PAGE analysis of SrtA-mediated ligation of 8 oxidoreductases after incubating for 36 h. Mono-oxidoreductases included oxidoreductase-mtf, oxidoreductase-GGGGSLPET and cyclized oxidoreductase-GGGGSLPET. Ligation products, mainly dimers and trimers, were labelled as crosslinked oxidoreductases.
Figure 8Thermal shift curves of 8 oxidoreductases and their crosslinked oxidoreductases.
…”
Section: Resultsmentioning
confidence: 99%
“…This increase in the thermal stability could be due to more covalent bonds between the monomers of crosslinked C1 enzyme than WT enzyme according to Xiang et al . 36 .
Figure 7SDS-PAGE analysis of SrtA-mediated ligation of 8 oxidoreductases after incubating for 36 h. Mono-oxidoreductases included oxidoreductase-mtf, oxidoreductase-GGGGSLPET and cyclized oxidoreductase-GGGGSLPET. Ligation products, mainly dimers and trimers, were labelled as crosslinked oxidoreductases.
Figure 8Thermal shift curves of 8 oxidoreductases and their crosslinked oxidoreductases.
…”
Section: Resultsmentioning
confidence: 99%
“…A series of haloalkane Uaas were designed and synthesized containing different halogen atoms linked with aliphatic chains of varying length (Figure 4B) [46]. The M. mazei tRNACUAPylPylRs pair was evolved to incorporate these Phe-scaffold Uaas [32] into myoglobin in E. coli and mammalian cells.…”
Section: Diverse Uaas Targeting Different Natural Amino Acid Residuesmentioning
confidence: 99%
“…ESI-FTMS analysis of mutant myoglobin showed that the Uaas were specifically incorporated and no side reaction of the Uaa with Cys, glutathione or any other amino acid residue was observed, indicating that the Uaa did not undergo modification or nonspecific self-reaction. These haloalkane Uaas, after incorporation into the affibody, react with a proximal Cys of the Z protein at the interface, crosslinking the two proteins irreversibly in the efficiency of ~45% in 1h [46]. Similarly, the Cl-PSCaa, 2-amino-3-(4-((3-(chloromethyl)phenyl)diazenyl)phenyl)propanoic acid, with benzyl chloride installed on an azobenzene was shown to be incorporated by the evolved tRNACUAPyl pair in E. coli and mammalian cells, and the incorporated Cl-PSCaa reacts with a proximal Cys to form an intramolecular photoswitchable bridge (Figure 4C) [47].…”
Section: Diverse Uaas Targeting Different Natural Amino Acid Residuesmentioning
confidence: 99%
See 2 more Smart Citations